The effect of sense of humor and empathy on the interpersonal adaptation. (October 2022) - Kim, Hwan; Choi, Hyera; Han, Sumi
Abstract: It is clear that sense of humor and empathy are personal qualities that have a positive effect on interpersonal relationships. To explore the influence of these two variables on interpersonal adaptation in detail, 309 remote university students were subjected to sense of humor, cognitive empathy, emotional empathy, interpersonal adaptation scales, and correlation analysis and regression analysis were performed. As a result of the correlation analysis, all variables of interest were significantly correlated, especially high with emotional empathy. In regression analysis, when entering emotional empathy as predictor, the explanatory power on interpersonal adaptation almost doubled. It seems to be important to focus on the emotional attributes when studying humor and interpersonal adaptation.